2016
DOI: 10.4149/neo_2016_013
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and Epstein-Barr virus in nasopharyngeal carcinoma in a non-endemic eastern european population

Abstract: Nasopharyngeal carcinoma (NPC) is a rare malignancy in the Czech Republic and Slovakia, with the standardized incidence rate of < 1:100000 person-years. Viral status of NPC in these non-endemic Eastern European regions is currently unknown. In a retrospective study, we evaluated the presence of EBV and HPV in 62 NPC cases. EBV status was determined by the use of in situ hybridization (ISH) for EBV encoded small RNA 1 (EBER1). HPV status was examined with p16 immunohistochemistry, DNA ISH and DNA polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
0
19
0
4
Order By: Relevance
“…It is widely accepted that EBV is etiologically associated with NPC in high‐incidence endemic regions, such as South‐Eastern China, but its significance in low‐incidence nonendemic countries has been equivocal . A recent meta‐analysis based on 8 studies of NPC in low‐incidence regions including the United States, the United Kingdom, Greece, and Denmark revealed that the prevalence of EBV positivity ranged from 0% to 83%, with an average of approximately 42% in solely white patients . In our nationwide series of Finnish patients with NPC, of which 97% were of white origin, EBV was detected in 62% of their tumors.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is widely accepted that EBV is etiologically associated with NPC in high‐incidence endemic regions, such as South‐Eastern China, but its significance in low‐incidence nonendemic countries has been equivocal . A recent meta‐analysis based on 8 studies of NPC in low‐incidence regions including the United States, the United Kingdom, Greece, and Denmark revealed that the prevalence of EBV positivity ranged from 0% to 83%, with an average of approximately 42% in solely white patients . In our nationwide series of Finnish patients with NPC, of which 97% were of white origin, EBV was detected in 62% of their tumors.…”
Section: Discussionmentioning
confidence: 70%
“…12 Studies from both endemic and nonendemic regions have reported the occurrence of HPV in NPC tumors, with or without the coexistence of EBV. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Unlike in oropharyngeal carcinoma, 32 no statistical significance for outcome has been attributed to HPV in NPC with 1 exception: Dogan et al reported that patients with HPV-positive tumor had, similarly to the patients with EBVpositive tumor, significantly better overall survival (OS) than the patients with EBV/HPV-negative tumor. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] In addition, Jiang et al suggested that although overexpression of p16 is not a significant prognostic marker for OS in NPC, it correlates with better progression-free survival and locoregional control in patients with EBV-positive tumor.…”
mentioning
confidence: 99%
“…Our study was not able to identify whether viral infection has a significant effect on survival because the SEER database does not contain these types of data. Recent studies suggest that this is an important issue even in non‐endemic regions such as the US, with 42% and 85% of NPC patients in American and Eastern European cohorts being EBV positive . EBV infection is associated with production of micro‐RNAs, one of which has been shown to affect the sensitivity of NPC cells to radiation therapy .…”
Section: Discussionmentioning
confidence: 99%
“…American and Eastern European cohorts being EBV positive. 38,39 EBV infection is associated with production of micro-RNAs, one of which has been shown to affect the sensitivity of NPC cells to radiation therapy. 40 This study had several limitations.…”
mentioning
confidence: 99%
“…Several studies suggest that EBV and HPV infections do not co-exist in NPC patients in West and East European countries [19, 20]. …”
Section: Hpv-positive Opcmentioning
confidence: 99%